Parameter Optimization for Dissimilar Aluminum Alloys Joined Using Friction Stir Additive Manufacturing: A Screening Study - Senthil Kumaran Selvaraj; Akash L. Manoj; Alan B. Mathew; Akash V. Govind; Govindaswamy Sundaramali; Utkarsh Chadha; Bhaskar Vajipeyajula; Albert E. Patterson (Engineering Reports)
ABSTRACT Due to the requirement for better strength‐to‐weight ratios, the utilisation of aluminum alloys is rapidly expanding. Lightweight components are of utmost importance in most industries, particularly in transportation, aviation, maritime, automotive, and other industries. These lightweight engineering materials are hard to be joined utilising traditional fusion joining techniques, necessitating the development of alternative joining techniques. The novel friction‐stir additive manufacturing (FSAM) technique, based on the concept of friction stir welding (FSW), can be used to combine aluminum alloys additively in their solid state. This work examines the effects of several process parameters (tool rotational speed, tool tilt angle, and tool transverse speed) on tensile strength and hardness using a 3‐factor L9 Taguchi designed experiment. Three cases were explored, one were AL 6061 was welded to AL 7075, one where AL 7075 was welded to AL 6061, and one where the data were mixed to get an “average” effect representative of large additively manufactured parts. A detailed ANOVA (including both main effects and interactions analyses) provided clear guidance on the optimization of the parameters for several objectives. This work will contribute to the development and wider use of FSAM in both industrial and academic research settings by providing a useful dataset and clear parameter selection guidance. The results of this research indicate that the FSAM methodology could be utilized to fabricate large defect‐free structures, which can be a suitable replacement for the traditional Al6061 material used in automotive and aerospace sectors.